2006
DOI: 10.1016/j.cub.2006.10.056
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: RhoE Is a Pro-Survival p53 Target Gene that Inhibits ROCK I-Mediated Apoptosis in Response to Genotoxic Stress

Abstract: The Rho family of GTPases regulates many aspects of cellular behavior through alterations to the actin cytoskeleton . The majority of the Rho family proteins function as molecular switches cycling between the active, GTP-bound and the inactive, GDP-bound conformations . Unlike typical Rho-family proteins, the Rnd subfamily members, including Rnd1, Rnd2, RhoE (also known as Rnd3), and RhoH, are GTPase deficient and are thus expected to be constitutively active . Here, we identify an unexpected role for RhoE/Rnd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…1C). RhoE, another member of the Rho family, has been identified as a p53-inducible gene in response to genotoxic agents (33). The authors of that study focused on upregulation of RhoE mRNA after long exposures to genotoxic agents, typically 12 h or longer.…”
Section: Resultsmentioning
confidence: 99%
“…1C). RhoE, another member of the Rho family, has been identified as a p53-inducible gene in response to genotoxic agents (33). The authors of that study focused on upregulation of RhoE mRNA after long exposures to genotoxic agents, typically 12 h or longer.…”
Section: Resultsmentioning
confidence: 99%
“…RhoE-luc, Hey2-luc, HES1-AB-luc, HES1-ΔAB-luc, and CSL-responsive luciferase reporter constructs were previously described (2, 5, 22). …”
Section: Methodsmentioning
confidence: 99%
“…It has been found that Rnd3 is a downstream target of p53, which favors cell survival through the inhibition of ROCK1-mediated apoptosis (100, 156). Ongusaha and co-workers showed that Rnd3 was transcriptionally induced in response to various DNA damaging agents, resulting in the disassembly of actin stress fibers.…”
Section: Physiological Function Of Rnd3mentioning
confidence: 99%
“…Ongusaha and co-workers showed that Rnd3 was transcriptionally induced in response to various DNA damaging agents, resulting in the disassembly of actin stress fibers. Knockdown of Rnd3 not only prevented the disassembly of the actin cytoskeleton, but also promoted apoptosis (100). However, it should be noted that inhibition of ROCK activity does not protect against apoptosis in all cell types, implying that additional factors likely contribute to the ultimate outcome (29).…”
Section: Physiological Function Of Rnd3mentioning
confidence: 99%